ANALYSIS OF THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND THE ABILITY TO EXERCISE POLICE DISCRETION - Fadli Hacarya Yusronnatika (INFOKUM, 2023)
The public's highest expectation for its police is the diligent execution of professional responsibilities with utmost professionalism. The National Police's repeated failures, which tarnish its reputation in society, can be attributed to the persistently low level of emotional intelligence inside the organization. The objective of this study is to establish the correlation between Emotional Intelligence and the Capacity to Exercise Police Discretion. This study will employ survey and interview methodologies to gather data from police officers working in the Samapta Unit of the Tasikmalaya City Police Resort. The data collection in this study involved the utilization of the Police Discretion Scale and the Emotional Intelligence Scale, which were administered to a sample of 70 participants. The analysis reveals a strong and statistically significant positive correlation (rxy = 0.501, p = 0.000, p<0.05) between emotional intelligence and discretion in police. Therefore, the hypothesis suggesting a positive relationship between emotional intelligence and discretion in the police Samapta function is supported.